Innovation of Early Talent Development of Primary Education Students Based on Total Quality Management - Badrus, Badrus; Rahman, Marita Lailia; Sulthon, Muhammad (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
The lack of creativity of parents and educational institutions in exploring children's talents can have an impact on the reduced innovation of student talent development. On a broader scale, the innovation of underdeveloped student talents can result in limited contributions to important work that may hinder the progress of various fields in the future. This research uses a qualitative descriptive method with the method of collecting observational data, interviews and documentation. While the data analysis uses Miles and Hubberman's theory, namely data reduction, data display and inference. The results showed that the teacher's strategy in identifying students' talents was carried out through four stages. First, internal exploration of the students by giving them freedom to choose the talents to be developed. Second, dealing with talent tests. Third, confirmation with parents. And fourth, final determination of talents. The talent development strategy is carried out through two channels. First, internal coaching path through madrasahs. And second, external coaching through course institutions and training in Madrasah Ibtidaiyah environment. To ensure the continuous growth of student talent, the madrasah collaborates with parents, course institutions and training through a mutually agreed Memorandum of Understanding (MoU). This form of cooperation is a new talent development management strategy that can provide progressive results for the development of student talent.